Numerical design optimisation for the Karoo Array Telescope - Joubert, N. J. D. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.